PENGARUH EMOTIONAL INTELLIGENCE TERHADAP QUARTER-LIFE CRISIS PADA GENERASI Z USIA 22-25 TAHUN - Vania Yus Veda; Maria Nugraheni Mardi Rahayu (Program Studi S1 Psikologi, 2023)
In the emerging adulthood period, individuals will face various developmental demands and more complex problems that make them vulnerable to entering a crisis stage which is called a quarter-life crisis. Takes a number of things that can help individuals to handle this crisis, one of which is emotional intelligence. Emotional intelligence is considered important to help individuals overcome the quarter-life crisis and be able to make the right decisions for their future. Therefore, the purpose of this study was to assess the effect of emotional intelligence on quarter-life crises in generation Z aged 22-25 years. The method used is quantitative with a simple regression statistical analysis process. There were 310 participants of Generation Z aged 22-25 years old in this research using an incidental sampling technique. The instrument in this study used The Developmental Crisis Questionnaire (α = 0.846) and The Emotional Intelligence Scale (α = 0.908). The results of this study show there is a significant influence between emotional intelligence on quarter-life crises. Emotional intelligence makes an effective contribution of 42.8% against quarter-life crises. The implication of this research is that generation Z aged 22-25 years old can improve their emotional intelligence to help them fulfill their developmental tasks and not get caught up in a quarter-life crisis.